Compound stimulus and social belonging: fiction, identity, and bond formation (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article investigates how the feeling of belonging can be understood and stimulated through theatrical practices. Focusing on an experience with young athletes from Coritiba Foot Ball Club, the research draws on theoretical foundations related to social belonging and its implications for identity and the formation of affective bonds. Inspired by principles of Drama, the approach used the compound stimulus as a pre-text to provoke immersion in fictional situations, awakening a sense of group belonging. The article argues for the centrality of belonging as a foundation for sensitive, emancipatory educational practices that value each subject’s uniqueness.
Keywords: social belonging; memory; drama; identity; theatre education